(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
For the protection of individual’s rights and liberties law was recognized as the mighty instrument. Whenever the right and liberty of an individual was encroached by another, the injured individual could seek the protection of law with the assistance of the king or sovereign however powerful the opponent (wrongdoer) might be. Sovereign’s power to punish keeps the people in righteous path. With the changing society and changed mindset of people the concept of righteousness has been diluted therefore the need of stringent laws were sought. The law, according to western jurisprudence, is an imperative command which is enforced by some superior power or sovereign. The objective of law is to promote and ensure justice. The principles of law provide certainty and uniformity to the justice administration system. The courts are the legal institutions which ensure the justice. The present paper would talk about the PIL as an instrument to poise the competing security and interests of different stakeholders in the society.